(untitled) (Research, Society and Development, 2020)
With the emergence and subsequent popularization of social networks, companies have been increasingly using this new media to get closer to their customers. In this sense, the research aimed to analyze how tourism agencies use their Facebook page to communicate with their customers. As for the method, the research is characterized as qualitative and quantitative. As a result, it was found that companies are concerned with the reaction of their users as to the type of content published on their pages. Another interesting fact to take into account is the high number of positive reactions that the companies ’publications obtained and it is possible to verify the level of satisfaction of the users in relation to the content of the companies’ pages. It is also concluded that the travel agencies that use Facebook as a tool to publicize their tourist products, face a great challenge to remain in the market, due to the fact that they are selling an intangible, untouchable product, which the customer must pay before , without being able to see or feel.